Nanobubble dynamics studied with transmission electron microscopy - Mohan, Meera Kanakamma (2016)
The study of nanoscale phenomena using in-situ transmission electron microscopy (TEM) has received increasing attention due to its ability to image at both high spatial and temporal resolution. In this study, nanobubbles forming within graphene liquid cells are characterised in TEM. It was observed that nanobubbles shrink quickly under illumination by an electron beam, but are stable for an hour or more in its absence. By observing the merger of nanobubbles, it was deduced that the apparent viscosity of the confined water in the graphene liquid cell is much larger than bulk water, and this reduces the diffusion constant to an extent that supports the long lifetime of the bubble. Apart from these observations, we also characterize instances of bubbles rupturing, oscillating, merging and non-coalescence events. Key Words: Nanobubble, Transmission Electron Microscope, nanobubble stability, bubble merger, bubble shrinkage, bubble rupture, bubble oscillations, diffusion, non-coalescence.